Ion channel structures: a review of recent progress. - Domene, C; Haider, S; Sansom, MS (2003)
Several ion channel structures have recently been determined, including MthK (a bacterial K+ channel in an open state), KirBac (a bacterial homolog of mammalian inward rectifier K+ channels), KvAP (a bacterial voltage-activated K+ channel) and the pore domain of the nicotinic acetylcholine receptor. Analysis of these structures has increased our understanding of the molecular mechanisms underlying channel gating. A hydrophobic gate appears to operate in a number of channels. Structures of ligand binding domains provide some clues as to how ligand-induced conformational changes control channel gating, but further experimental and computational studies are required before a full picture emerges.